The Impact of Regional Economic Conditions on the Efficiency of Savings Banks in the Light of Demographic Change - Alexander Conrad; Doris Neuberger; Lucinda Trigo Gamarra (Credit and Capital Markets – Kredit und Kapital, 2014)
This paper examines the influence of environmental factors on the technical and revenue efficiency of German savings banks. It employs a two-step approach, using, first, data envelopment analysis to calculate efficiency and, second, multivariate regressions to examine the influence of regional economic conditions on efficiency. Taking into account demographic change with growing regional disparities in economic wealth and population, it differentiates between declining and growing regions and finds that regional factors explain 10–20 % of the variation in efficiency levels. Competitive pressure is the most important environmental factor affecting efficiency, consistent with the quiet life hypothesis. Higher population density and branch penetration enhance efficiency in growing regions while, in declining regions, a greater percentage of older people reduces bank efficiency. Demographic changes through population aging and migration from poor to rich regions impair the efficiency of banks in declining, peripheral regions. Our results show that the public mission of providing financial services to all regions has its costs in terms of efficiency losses. On the other hand, the regional principle of the savings banks sector guarantees competition between banking groups in most regions, which has the largest impact on efficiency. – – Der Einfluss regionalökonomischer Faktoren auf die Effizienz von Sparkassen angesichts des demografischen Wandels Der Beitrag untersucht den Einfluss von Umfeldfaktoren auf die technische Effizienz und Ertragseffizienz deutscher Sparkassen. Mit einem zweistufigen Verfahren – Data Envelopment Analyse im ersten Schritt und multivariate Regressions-analysen im zweiten Schritt – wird der Einfluss regionalökonomischer Faktoren auf die Effizienz untersucht. Angesichts des demografischen Wandels mit zunehmenden regionalen Disparitäten in Wohlstand und Bevölkerung wird zwischen schrumpfenden und wachsenden Regionen differenziert. Regionale Faktoren erklären 10–20 % der Effizienz unterschiede. Der wichtigste externe Einflussfaktor auf die Effizienz ist der Wett bewerbs druck, entsprechend der "quiet life"-Hypothese. Mit zunehmender Bevölkerungs- und Filialdichte steigt die Effizienz in wachsenden Regionen, während sie in schrumpfenden Regionen mit dem Anteil älterer Menschen sinkt. Demografischer Wandel durch Bevölkerungsalterung und Migration von armen zu reicheren Regionen beeinträchtigt die Effizienz von Banken in schrumpfenden, peripheren Regionen. Der öffentliche Auftrag der Sparkassen, eine flächendeckende Versorgung mit Finanz dienstleistungen sicherzustellen, verursacht damit Kosten in Form von Effizienz verlusten. Andererseits wird durch das Regionalprinzip der Wettbewerb zwischen den Bankengruppen in den meisten Regionen sichergestellt, wovon die größte effizienzsteigernde Wirkung ausgeht.
Keywords: G21; D24; L2; R1; 330; revenue efficiency; technical efficiency; Data Envelopment Analysis; savings banks; demographic change